1996
DOI: 10.1165/ajrcmb.15.1.8679225
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the urokinase receptor in fibroblasts from normal and fibrotic human lungs.

Abstract: Binding of urokinase-type plasminogen activator (uPA) to a specific receptor (uPAR) on human lung fibroblasts enables it to regulate cellular proteolysis and remodeling of the extracellular matrix. Binding studies with radiolabeled uPA indicated that both normal and fibrotic lung fibroblasts express the receptor, but cells from fibrotic tissues bound significantly more uPA (P < 0.001). Phorbol myristate acetate, lipopolysaccharide, transforming growth factor-beta (TGF-beta), and tumor necrosis factor-alpha (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 32 publications
4
55
0
1
Order By: Relevance
“…The increase of PA-dependent activity and PA mRNA at the crush site within 1 d of crush could be attributed to reactive and infiltrating neutrophils, macrophages, fibroblasts, and Schwann cells into the area of injury. All of these cell types express components of the PA system (Eaton et al, 1984;Heiple and Ossowski, 1986;Wilson and Francis, 1987;Grau and Moroz, 1989;Varani et al, 1992;Kung and Lau, 1993;Schafer et al, 1994;Rao et al, 1995;Kindzelskii et al, 1996;Shetty et al, 1996;Xiao et al, 1998). Additionally, we demonstrated with immunostaining that macrophages and neutrophils were present at the crush site within 1 d after crush injury (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…The increase of PA-dependent activity and PA mRNA at the crush site within 1 d of crush could be attributed to reactive and infiltrating neutrophils, macrophages, fibroblasts, and Schwann cells into the area of injury. All of these cell types express components of the PA system (Eaton et al, 1984;Heiple and Ossowski, 1986;Wilson and Francis, 1987;Grau and Moroz, 1989;Varani et al, 1992;Kung and Lau, 1993;Schafer et al, 1994;Rao et al, 1995;Kindzelskii et al, 1996;Shetty et al, 1996;Xiao et al, 1998). Additionally, we demonstrated with immunostaining that macrophages and neutrophils were present at the crush site within 1 d after crush injury (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…It has been shown that the expression of u-PAR is required for angiogenesis 23 and both TGF␤1 and CTGF genes are known to induce angiogenesis. 19,20 The observation that u-PAR is expressed in fibrotic fibroblasts and is responsible for cell migration and chemtotaxis, 24,25 which are also known functions of CTGF and TGF␤1, indicates that u-PAR may be induced by CTGF and TGF␤1 in wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic renal tubulointerstitial disease the induction of endogenous uPAR reduces fibrosis severity while in a model of crescentic glomerulonephritis, genetic deficiency of either uPA or uPAR did not worsen glomerulosclerosis although the degree of glomerular inflammation was reduced in the uPAR−/− mice (22,50). In humans uPAR expression levels are higher on fibroblasts isolated form fibrotic lungs compared to normal lungs (123). In human keloid compared with normal scars, uPAR expression is enhanced (124).…”
Section: Role Of Upa and Upar During Fibrogenesis: Disease And Organ mentioning
confidence: 99%